Module Development of Premarital Guidance for Buddhist Couples - Gunawinata, Vensi Anita Ria (Faculty of Psychology, Universitas Surabaya, 2011)
Buddhist couples who are going to get married view marriage as something romantic, andsee it as something that simple and fun, which makes them unaware of the problems thatcould emerge in a marriage. The purpose of this study was to develop a module as guidancefor premarital Buddhist couples, and to know the advantages and impact of the module forthe couples. Data were collected by using purposive sampling. Data were analyzed using acombination of quantitative and qualitative analyses techniques for the survey, assessmentand intervention. The assessment and dissemination of the module show that: (1) Buddhistcouples need precise information about marriage to evaluate optimistic and heuristic thoughts,(2) the module has been evaluated concerning its content, exercise and face validity and hasbeen valued good by experts, Buddhist monks, and premarital couples, (3) participants inthis study felt they have gain a lot of advantages after reading the module. Pasangan Buddhis yang hendak menikah memandang pernikahan dengan sudut pandangromantisme, menganggap pernikahan sebagai sesuatu hal yang sederhana dan menyenangkan,sehingga tidak menyadari masalah yang akan timbul dalam sebuah pernikahan. Tujuanpenelitian ini adalah mengembangkan modul persiapan pranikah bagi pasangan Buddhis danmengetahui manfaat dan dampak modul tersebut bagi pasangan Buddhis. Para subjekdiperoleh melalui purposive sampling. Data dianalisis dengan kombinasi analisis kuantitatifdan kualitatif pada data tahap survei, asesmen, dan intervensi. Hasil penelitian asesmen dandiseminasi modul menunjukkan bahwa: (1) pasangan muda-mudi Buddhis memerlukaninformasi yang tepat mengenai pernikahan untuk mengevaluasi pemikiran optimisme yangtidak realistis dan pemikiran heuristik, (2) modul yang dibuat telah dievaluasi secara isimateri, soal latihan, dan tampilan dan mendapatkan tanggapan nilai yang baik dari ujipakar, pandita vihara dan pasangan yang hendak menikah, (3) partisipan dalam penelitianini mendapatkan manfaat setelah membaca modul persiapan pranikah.